2013
DOI: 10.1002/clen.201200566
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite Resistance, Accumulation, and Volatilization Properties of Trichoderma asperellumSM‐12F1, Penicillium janthinellumSM‐12F4, and Fusarium oxysporum CZ‐8F1

Abstract: It is expected that microorganisms capable of arsenic (As) accumulation and volatilization can be used to remediate As‐contaminated environments. In this paper, the arsenite [As(III)] resistance, accumulation, and volatilization properties of Trichoderma asperellum SM‐12F1, Penicillium janthinellum SM‐12F4, and Fusarium oxysporum CZ‐8F1 were investigated. The results indicated that all three fungal strains exhibited significant As(III)‐resistance. After being exposed to 40 and 80 mg/L As(III) for five days, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…2b, d, and f). This result is consistent with our previous report (Feng et al, 2013), which indicated that As(III) can be adsorbed onto and accumulated into fungal cells. It is known that As(III) can bind to many chelating proteins or peptides containing thiol ligands, such as glutathione (GSH), phytochelatins (PCs), and metallothioneins (MTs) to form inactive complexes (Cobbett and Goldsbrough, 2002;Ngu et al, 2008).…”
Section: As(iii) Influx and Efflux Across The Fungal Cell Membranesupporting
confidence: 95%
See 2 more Smart Citations
“…2b, d, and f). This result is consistent with our previous report (Feng et al, 2013), which indicated that As(III) can be adsorbed onto and accumulated into fungal cells. It is known that As(III) can bind to many chelating proteins or peptides containing thiol ligands, such as glutathione (GSH), phytochelatins (PCs), and metallothioneins (MTs) to form inactive complexes (Cobbett and Goldsbrough, 2002;Ngu et al, 2008).…”
Section: As(iii) Influx and Efflux Across The Fungal Cell Membranesupporting
confidence: 95%
“…The As accumulation and volatilization abilities of three fungal strains, Trichoderma asperellum SM-12F1, Penicillium janthinellum SM-12F4, and Fusarium oxysporum CZ-8F1, have been detailed in previous reports (Zeng et al, 2010;Feng et al, 2013). The possible speciation of As in these fungal cells has been studied after exposure to arsenate [As(V)] (Su et al, 2011(Su et al, , 2012, which is a ubiquitous specie of As in oxic environments.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fungal resistance to As(V) in the environment has a certain tolerance threshold, and As(V) concentrations higher than the threshold value may affect the growth of fungi. 27 …”
Section: Resultsmentioning
confidence: 99%
“…Microorganisms have evolved various mechanisms to deal with As toxicity, including reducing the number of intracellular As molecules and biotransformation of As species by oxidation, reduction, and methylation. 27 , 28 It is reported that fungi living in As-contaminated sites have evolved different cellular and molecular systems to survive and have unique merits, such as high bioaccumulation and tolerance to As, high cell wall binding capacity, and high intracellular As uptake capacity. 29 32 To date, the bioaccumulation and tolerance of As(V) by fungi have been extensively reported upon, 33 35 whereas less information about fungal immobilization for As(V) bioremediation is available.…”
Section: Introductionmentioning
confidence: 99%